The identification of novel peptides using phage display with the potential for use in breast cancer therapy - Siebke, Christina (Trinity College (Dublin, Ireland). Department of Microbiology, 2011)
Breast cancer is a leading cause of cancer-related mortality in women. Current treatments for breast cancer include surgery, radiotherapy, chemotherapy and hormone therapy. The recent development of Herceptin has added a new category of treatments available for breast cancer, in the form of monoclonal antibodies which are aimed at targeting specific proteins which are over-expressed or altered in cancer. However there remains a need for the development of more specifically targeted breast cancer treatments. This project aimed to use phage-peptide display libraries to identify novel peptides that could bind specifically to breast tumour cells. Phage-peptide display libraries consist of genetically modified bacteriophage (phage) which have been engineered to express a vast array of different peptides on their surface. The display of these peptides on the phage surface allows for interaction with other proteins. By incubating a target protein of interest with a phage library, peptides with binding affinity to the target protein can be isolated and amplified. This step can be repeated numerous times to allow for the identification of peptides with high binding affinity for the target protein and this process is termed bio-panning.
Keywords: Microbiology, Ph.D.; Ph.D. Trinity College Dublin